Survey on the Implementation of the Cape Town Global Action Plan for Sustainable Development Data - World Bank; UNSD; Paris21 (World Bank, Washington, DC, 2022)
Since its launch in January 2017 at the first UN World Data Forum in South Africa, and its formal adoption by the United Nations Statistical Commission at its forty-eighth session in March 2017, the Cape Town Global Action Plan for Sustainable Development Data (CTGAP) has provided a framework for planning and implementing the statistical capacity building activities needed to achieve the scope and intent of the 2030 agenda for sustainable development, and to mobilize funding for the modernization of national statistical systems across the world. However, when the Coronavirus (COVID-19) pandemic hit the world in early 2020, national statistical authorities and the international statistical community inevitably shifted their attention to the immediate challenge of ensuring the continuity of the most basic statistical operations, and to addressing new, urgent data demands. As a consequence, significant resources were diverted away from longer-term initiatives aimed at achieving the shared goals crystallized in the commitment and vision of the CTGAP. This report presents the results of a survey conducted by the World Bank, the United Nations Statistics Division (UNSD), and PARIS21, with the aim to inform actions by decision makers and international partners to implement, monitor, and finance the CTGAP. This last survey was launched with the purpose of seeing beyond the immediate crisis, and to ensure that the current constraints do not distract attention from the common goals enshrined in the 2030 agenda for sustainable development and the implementation of the CTGAP.